Analisis Break Even Point (BEP) sebagai Dasar Pengambilan Keputusan dalam Pemilihan Tungku pada UKM Keripik Tempe - Hety Handayani Hidayat; Dian Novitasari (Manajemen Agribisnis: Jurnal Agribisnis, 2021)
The stove selection in Tempe chips SMEs is one of the crucial things done in the planning process as an effort to reduce production costs. Especially for SMEs whose more complex production process, namely producing their own tempes. So this study aims to examine the production cost as a break-even point (BEP) analysis of stove type choices as a basis for determining the right stove. This BEP analysis includes manufacturing investment costs, fuel costs, educational costs for technological changes, production quantities and capacity of each stove type. From the research results is known that the production cost by using conventional stove is Rp. 21.53 per unit, but with energy saving stoves only Rp. 14.2 per unit. Because of that, Tempe Yu Mudah Chips is recommended for using energy-efficient stoves in the production process.